2011
DOI: 10.3109/s10165-010-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing surveillance of safety and effectiveness of etanercept in Japanese patients with rheumatoid arthritis

Abstract: Our aim was to evaluate real-world safety and effectiveness in a 6-month postmarketing surveillance study covering all Japanese patients with rheumatoid arthritis (RA) who received etanercept during a 2-year period. Data for 13,894 patients (1334 sites) enrolled between March 2005 and April 2007 were collected. Adverse events (AEs) and serious adverse events (SAEs) were reported in 4336 (31.2%) and 857 (6.2%) patients, respectively. The most frequent AEs were injection site reactions (n = 610, 4.4%) and rash (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 20 publications
7
31
0
Order By: Relevance
“…Several patients had diffuse B cell lymphoma, which is known to occur with increased frequency in patients with RA 37 . IR of lymphoma observed here were comparable with those observed with other biologic agents 24,30 , and registry data suggest that biologics are not associated with any further increase in the already elevated lymphoma occurrence in RA 38 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Several patients had diffuse B cell lymphoma, which is known to occur with increased frequency in patients with RA 37 . IR of lymphoma observed here were comparable with those observed with other biologic agents 24,30 , and registry data suggest that biologics are not associated with any further increase in the already elevated lymphoma occurrence in RA 38 .…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies 15,24,25,26,27 have demonstrated an increase in serious infections, such as pneumonia and TB, in patients receiving some anti-TNF therapies compared with other biologic or nonbiologic DMARD. The IR of serious infection among patients treated with IV abatacept presented in our study was similar to, or less than, that previously reported in other integrated or pooled safety analyses of biologic agents in RA 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate logistic regression analysis identified the following risk factors for serious infection: age ≥ 65 years, longer disease duration (≥ 10 yrs), previous or concurrent respiratory disease, and mean concomitant corticosteroid dose > 5 mg/day (prednisolone equivalent). The risk factors for serious infection identified in our study are similar to the findings reported from the all-patient PMS conducted for infliximab, etanercept, and adalimumab in Japan 1,13,14,15 . Patients with 3 or more of these risk factors had a cumulative incidence of serious infection about 10 times that of patients with no risk factors.…”
Section: Rheumatologysupporting
confidence: 79%
“…Patients undergoing anti-TNF therapy frequently develop extrapulmonary tuberculosis (1)(2)(3)(4). However, it remains unknown whether this high frequency of extrapulmonary tuberculosis is a characteristic of RA patients undergoing anti-TNF therapy or whether anti-TNF therapy is not a factor in RA patients, as the characteristics of tuberculosis infection in RA patients treated without anti-TNF therapy have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%